2019
DOI: 10.1016/j.cmi.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Saliva as a diagnostic specimen for testing respiratory virus by a point-of-care molecular assay: a diagnostic validity study

Abstract: Saliva specimen has high sensitivity and specificity in the detection of respiratory viruses by an automated multiplex Clinical Laboratory Improvement Amendments (CLIA)-waived point-of-care molecular assay when compared with that of NPA. The use of saliva also reduces the time and cost associated with specimen collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
164
0
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(178 citation statements)
references
References 25 publications
7
164
0
7
Order By: Relevance
“…If patients were intubated, we obtained endotracheal aspirate instead of posterior oropharynx saliva. 6,[9][10][11] Our initial experience showed that such saliva samples are promising in viral load monitoring in patients with COVID-19. 6 We also retrieved serum remnant from blood samples taken for routine bio chemical testing, and refrigerated these samples at -20°C until antibody testing could be done.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If patients were intubated, we obtained endotracheal aspirate instead of posterior oropharynx saliva. 6,[9][10][11] Our initial experience showed that such saliva samples are promising in viral load monitoring in patients with COVID-19. 6 We also retrieved serum remnant from blood samples taken for routine bio chemical testing, and refrigerated these samples at -20°C until antibody testing could be done.…”
Section: Methodsmentioning
confidence: 99%
“…Findings of previous studies have shown high concordance between saliva and nasopharyngeal aspirate as specimens for laboratory diagnosis of respi ratory viruses. 9 We have reported use of posterior oro pharyngeal (deep throat) saliva for diagnosis and viral load monitoring in a cohort of 12 patients with COVID-19. 6 Here, we report use of self-collected posterior oro pharyn geal saliva samples from patients with COVID-19, which avoids close contact between healthcare workers and patients, for viral load monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory samples of the patients were tested for influenza A and B viruses and respiratory syncytial virus using the Xpert Xpress Flu/RSV assay (GeneXpert System, Cepheid, Sunnyvale, CA, USA) according to the manufacturer's instructions. 6 To detect the presence of 18 respiratory virus targets and four bacteria (including adenovirus, coronaviruses [HCoV-229E, HCoV-Nl63, HCoV-Oc43, HCoV-HKU1, and MERS-CoV], human metapneumovirus, respiratory syncytial virus, human rhinovirus or entero virus, influenza A viruses [H1, H1-2009 and H3], influenza B virus, parainfluenza viruses [types 1 -4], Bordetella pertussis, Bordetella parapertussis, Chlamydophila pneumoniae, and Mycoplasma pneumoniae), samples were tested using BioFire FilmArray Respiratory Panel 2 plus (bioMérieux, Marcy l'Etoile, France) according to the manufacturer's instructions. 7 The two faecal samples were taken from the patients who had diarrhoea as part of their symptoms, and the samples were tested by BioFire FilmArray Gastrointestinal panel (bioMérieux) for 22 diarrhoeal pathogens.…”
Section: Respiratory and Diarrhoeal Pathogen Detectionmentioning
confidence: 99%
“…Since no invasive procedures are required, the collection of saliva can greatly minimize the chance of exposing healthcare workers to 2019-nCoV. We have previously demonstrated that saliva has a high concordance rate of greater than 90% with nasopharyngeal specimens in the detection of respiratory viruses, including coronaviruses [5,6]. In some patients, coronavirus was detected only in saliva but not in nasopharyngeal aspirate [5].…”
mentioning
confidence: 99%